The Impact of Acquisitions on the Productivity of Inventors at Semiconductor Firms: A Synthesis of Knowledge-Based and Incentive-Based Perspectives - Kapoor, Rahul; Lim, Kwanghui (Academy of Management Journal, 2007)
We show how knowledge-based and incentive-based perspectives complement each other to explain the effects of acquisitions on the productivity of inventors from acquired firms. Incentive-based theories account for their lower productivity relative to that of inventors at nonacquired firms, and both perspectives jointly explain why their productivity converges with that of inventors from acquiring firms. Higher productivity is achieved when there is greater overlap in routines and moderate overlap in skills, and when the acquired firm is large relative to its acquirer. This study clarifies the subtle manner in which incentives and the knowledge-based view are intertwined.